Engraving and etching, 1400-2000 : a history of the development of manual intaglio printmaking processes - Stijnman, Ad. (London : Archetype Publications ; Houten, Netherlands : in association with HES and DE GRAAF Publishers, 2012)
"This comprehensively illustrated study is the first of its kind to cover all elements of the trade of engraving and etching throughout six centuries"--Publisher's website.
Introduction. Origin and structure of this study ; Art history and printmaking ; Main issues ; Technique and style ; Working method -- Antecedents, early developments and dissemination. Engraving ; Intaglio printing ; Etching ; Dissemination of intaglio printmaking techniques -- The trade in intaglio printmaking. Engravers and plate printers ; Education ; The workshop ; Suppliers -- Producing the Matrix. The printing plate ; Transferring the design ; Mechanical procedures ; Chemical procedures ; Non-manual procedures -- Printing the matrix. General ; Printing support ; Printing medium ; Printing press ; Printing procedures ; Colour printing procedures -- Summary and final conclusions -- Appendix 1: General chronology of intaglio printmaking processes -- Appendix 2: Early engravers up to 1500 -- Appendix 3: Terms in print addresses.
Includes bibliographical references and index.
Keywords: Intaglio printing; Intaglio printing -- History